ANALISIS REKONSTRUKSI SISTEM PEMASYARAKATAN BERBASIS VIKTIMOLOGI DITINJAU DARI PERSPEKTIF PERLINDUNGAN HAK KORBAN DALAM HUKUM DI INDONESIA - Ikama Dewi Setia Triana; Eti Mul Erowati; Elisabeth Pudyastiwi; Elly Kristiani Purwendah (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This study aims to analyze the urgency of implementing the victimology paradigm in the Indonesian correctional system, particularly in the context of protecting the rights of victims of crime. To date, the correctional system has focused more on the development of prisoners as perpetrators, while the role and position of victims tend to be neglected. This is despite the fact that Law Number 22 of 2022 concerning Corrections mandates the principle of protecting victims' rights. Using normative legal research methods and a legislative approach, this study examines legal doctrine, theory, and regulations related to victimology and correctional services. The results show that integrating victimology into the correctional system not only fulfills formal legal aspects but is also crucial for achieving substantive justice goals. The concept of restorative justice serves as an important bridge to integrate the interests of victims, perpetrators, and society. Therefore, this study recommends the need for philosophical and legal reconstruction of the correctional system to be more responsive to the needs of victims, making corrections not merely a place of development but also a forum for recovery and justice for all parties.